2011
DOI: 10.1111/j.1745-459x.2011.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Naturally Brewed Soy Sauce to Reduce Salt in Selected Foods

Abstract: The aim of this study was to explore the use of soy sauce to reduce salt intake in daily food preparation by replacing all or some added salt with naturally brewed soy sauce without change in consumer acceptance. Three types of foods were investigated: salad dressing, tomato soup and stir-fried pork. A two-alternative forced choice test between a salt standard and a variety of soy sauce samples was used to establish the exchange rate, giving the amount of soy sauce needed to replace added salt with the same ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Salt reduction by increasing the moisture content and decreasing the fat content [92] Use of potassium chloride [94] 1:1 mixture of sodium chloride with potassium chloride [95] Use of potassium based emulsifying salts (DPP, TPC) in processed cheese [91,98] Saltiness enhancement by specific odors (cheese/sardine aroma) [127] Soups General reduction of sodium by almost 50% without affecting consumer acceptance [105] Sodium reduction of 17%-33% by the use of naturally brewed soy sauce [106,129] Salt reduction of 15% can be compensated by savory aroma compounds (beef/chicken flavor) [126] Water-in-oil-in-water emulsions [64] Ready meals Reduction of sodium by 30-40% without affecting consumer preference [100][101][102] Use of salt substitutes (e.g. potassium chloride) and flavor enhancers (e.g.…”
Section: Meats and Meat Productsmentioning
confidence: 99%
“…Salt reduction by increasing the moisture content and decreasing the fat content [92] Use of potassium chloride [94] 1:1 mixture of sodium chloride with potassium chloride [95] Use of potassium based emulsifying salts (DPP, TPC) in processed cheese [91,98] Saltiness enhancement by specific odors (cheese/sardine aroma) [127] Soups General reduction of sodium by almost 50% without affecting consumer acceptance [105] Sodium reduction of 17%-33% by the use of naturally brewed soy sauce [106,129] Salt reduction of 15% can be compensated by savory aroma compounds (beef/chicken flavor) [126] Water-in-oil-in-water emulsions [64] Ready meals Reduction of sodium by 30-40% without affecting consumer preference [100][101][102] Use of salt substitutes (e.g. potassium chloride) and flavor enhancers (e.g.…”
Section: Meats and Meat Productsmentioning
confidence: 99%
“…To satisfy the expectations of European Nutrition claims, agrifood companies have to decrease the amount of salt, fat and sugar in 30% of their products. However, these ingredients are known to contribute to consumer appreciation; therefore, changing the formulation process may endanger the sensory quality of these products (Brauss, Linforth, Cayeux, Harvey, & Taylor, 1999;Drewnowski & Greenwood, 1983;Drewnowski, Nordensten, & Dwyer, 1998;Goh et al, 2011;Zoulias, Oreopoulou, & Kounalaki, 2002). A major challenge is to maintain consumer appreciation and consumption while offering healthier food products for the consumer.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of ingredients containing salty-potentiating compounds such as umami, for example, has been shown to not only enhance the salty taste but also other tastes and flavor notes of food products (Fuke and Ueda 1996;Keast and Breslin, 2002). Traditionally brewed soy sauce (SS; comprised of water, NaCl, soybeans, and wheat) and fermented flavor enhancer (NFE; comparable to SS but manufactured to possess less soy flavor, a lighter color, and umami flavor amplification) are 2 ingredients of particular interest for this research as they both contain high levels of umami substances generated through a fermentation process from contributing amino acids and peptides (Fukushima, 2004;Kremer et al, 2009;Goh et al, 2011;Jiménez-Maroto et al, 2013;Kremer et al, 2013a;Kremer et al, 2013b;Shimojo et al, 2014). Recent research (McGough, 2011;McGough et al, 2012a;McGough et al, 2012b) has shown the use of SS and NFE can be successfully implemented into a sodium reduction system for frankfurters where sodium reduction of 20% singly or 35% in combination with KCl were achieved with no significant (P > 0.05) impact on quality or consumer acceptance.…”
Section: Introductionmentioning
confidence: 99%